2015
DOI: 10.1089/jir.2014.0036
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Interleukin-21 Receptor on B Cells Associated with the Downregulation of IgE in Patients with Allergic Rhinitis

Abstract: Allergic diseases, such as allergic rhinitis, caused by an immunoglobulin E (IgE)-mediated reaction to specific allergens are a common chronic condition worldwide. Interleukin-21 (IL-21), a type I cytokine that is produced by T cells, exerts regulatory effects on a variety of immune cells. In our previous study, we found that serum levels of IL-21 were significantly decreased in patients with severe atopic dermatitis, suggesting that IL-21 might play a role in allergic reactions. In this study, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Meanwhile, Hsiao-Yu et al observed high expression of IL-21 receptor on naive and memory B cells in AR patients. 34 This was in line with the high levels of IL-21 and IgE in serum in AR patients. IL-21 could drive more B cells to differentiate into plasma cells to secrete immunoglobulin, including IgE, which likely contributes to the pathogenesis of AR.…”
Section: Discussionsupporting
confidence: 74%
“…Meanwhile, Hsiao-Yu et al observed high expression of IL-21 receptor on naive and memory B cells in AR patients. 34 This was in line with the high levels of IL-21 and IgE in serum in AR patients. IL-21 could drive more B cells to differentiate into plasma cells to secrete immunoglobulin, including IgE, which likely contributes to the pathogenesis of AR.…”
Section: Discussionsupporting
confidence: 74%
“…Production of specific IgE, IL-4, and IL-5 was reduced in CD40 -/and Schistosoma mansoni egg antigeninduced AR mouse models [23]. IgE secretion by B cells was inhibited by promoting the combination of CD40L and IL-4 in patients with AR [24]. Recently, siRNA is used in studies of the role of CD40 in allergic inflammation.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…A decreased in IgE+ B cells proportion was found in AR patients after AIT without correlation between blood IgE+ B cells and circulating IgE levels [ 59 ]. There is evidence that IL-21 regulates IgE levels by binding to B cells in the AR associated immune response [ 60 ]. Regulatory B cells (B regs ) modulate inflammation by IL-10, IL-35 and TGF-ß secretion and are associated with allergen tolerance [ 61 ].…”
Section: Blood Cells In Armentioning
confidence: 99%